Audit Tenure, Auditor Rotation, and Audit Quality: The Case of Indonesia - Siregar, Sylvia Veronica; Amarullah, Fitriany; Wibowo, Arie; Anggraita, Viska (Asian Journal of Business and Accounting, 2012)
The Indonesian regulators have made it compulsory to rotate the appointments of public accountants every 3 years and the appointment of public accounting firms every 5 years, since the end of 2002. The purpose of this study is to investigate the effects of auditor rotation and audit tenure of the public accountant and the public accounting firm, on audit quality (before and after the implementation of the mandatory auditor regulation). The results do not support that mandatory auditor rotation increases audit quality or that a shorter audit tenure (both partner and firm level) increases audit quality. Regulators may need to consider revising the regulation (i.e. related to maximum years allowed for auditor to audit their client) and/or introduce other regulations to increase audit quality. Keywords: Audit rotation, Audit tenure, Audit quality, Discretionary accrual